Contemporary Art On Fashion In Jember Fashion Carnaval (2016-2021) - Bramantijo, Bramantijo; Aprilia Lani Kartini, Rose (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
As a fashion show that includes members of all societal strata, Jember Fashion Carnival (JFC) is regarded as a must-attendcultural event in East Java. In modern civilization, fashion is used as a means of communication to express social, cultural, andpersonal identity. Art and fashion share many similarities in how they portray or convey feelings, expression, amusement, and beingpresented. The term experimental, a subset of contemporary art, has its roots in the creation of clothing that pushes the boundariesof both fashion and performance art, or as it is known in the language of fashion, the avant-garde. This study intends toascertain the evolution of contemporary art at JFC as well as the impact of contemporary art on fashion at JFC events, particularlyfrom 2016 to 2021. The data gathered were examined inductively as a cultural inquiry utilizing ethnographic techniques. The visualcultural portion includes shape, color, texture, fashion, and the arts. Regarding poetry and how to develop and connect ideas, theaesthetics of art and fashion are similarly similar. Avant-garde fashion is contemporary art applied, yet one might also say thatfashion is a costume in contemporary art. In JFC, the focus is on the artists' creative processes, and how innocence and wildness intheir work emerge. They also receive guidance and instruction on creating, applying makeup, walking, and dancing.The Jember Fashion Carnival not only has a theme but also emphasizes the theatricality and soul of the costumes. Values, excitement, and motivation to create fashion pieces fuel the carnival's rebirth. In addition, each theme also incorporates components of values, culture, humanism, compassion, and openness to different viewpoints.